Fuentes de financiamiento de las micro y pequeñas empresas familiares del sector confección de Barranquilla (2021)
Companies continue to search for economic resources to maintain their operations or to increase production levels and grow, however, this has become a challenge that often ends in the decline of business activities, especially in the smaller ones. Under these considerations, this study analyzes the sources of financing used by micro and small family businesses in the clothing sector of Barranquilla - Colombia. For this, a descriptive cross-sectional methodology was used, with a field design, applying a questionnaire of 27 items to owners or administrators of 93 economic entities. The results reveal that: a) 86.7% of the entities have been operating for less than 10 years. b) 68.9% of the businesses are in the hands of the first generation of the family. c) In the short term, 71.1% of the sector uses its own resources to finance itself (savings or reinvestment of profits), as well as external loans (family, friends and informal loans). d) In the long term, 22.2% is financed again with own resources, external and bank loans, ruling out the issuance of shares, bonds and leases. It is concluded that these micro and small companies are new to the market, with survival problems, without greater support from public or private institutions that promise funds for small enterprises, so strategies must be considered to finance the normal development of operations and motorize their growth, taking advantage of the family bond that characterizes them to ensure their continuity in the sector.